Splenic artery aneurysms – a systematic review of the literature - Marta Machado; Andreia Coelho; João Peixoto; Luís Fernandes; Roberto Boal; Francisco Basílio; Patrícia Carvalho; Beatriz Guimarães; Pedro Brandão; Alexandra Canedo (Angiologia e Cirurgia Vascular)
INTRODUCTION: Splenic artery aneurysms (SAA) are the most frequent (50 to 75%) abdominal visceral arterial aneurysms. In autopsy studies, the overall incidence is 0.01%, increasing to 10.4% with age. Due to their rarity, there is a lack of data, so we aimed to perform a systematic review of available SAA data.